Non-variceal upper gastrointestinal bleeding - Lanas, A; Dumonceau, J; Hunt, R; Fujishiro, M; Scheiman, J; Gralnek, I; Campbell, H; Rostom, A; Villanueva, C; Sung, J (Nature Publishing Group, 2018)
Non-variceal upper gastrointestinal bleeding (NVUGIB) is bleeding that develops in the oesophagus, stomach or proximal duodenum. Peptic ulcers, caused by Helicobacter pylori infection or use of NSAIDs and low-dose aspirin (LDA), are the most common cause. Although the incidence and mortality associated with NVUGIB have been decreasing owing to considerable advances in the prevention and management of NVUGIB over the past 20 years, it remains a common clinical problem with an annual incidence of ∼67 per 100,000 individuals in the United States in 2012. NVUGIB is a medical emergency, and mortality is in the range ∼1-5%. After resuscitation and initial assessment, early (within 24 hours) diagnostic and therapeutic endoscopy together with intragastric pH control with proton pump inhibitors (PPIs) form the basis of treatment. With a growing ageing population treated with antiplatelet and/or anticoagulant medications, the clinical management of NVUGIB is complex as the risk between gastrointestinal bleeding events and adverse cardiovascular events needs to be balanced. The best clinical approach includes identification of risk factors and prevention of bleeding; available strategies include continuous treatment with PPIs or H. pylori eradication in those at increased risk of developing NVUGIB. Treatment with PPIs and/or use of cyclooxygenase-2-selective NSAIDs should be implemented in those patients at risk of NVUGIB who need NSAIDs and/or LDA.